Adsorption of Pb(II), Cu(II) and Cd(II) from aqueous solution by natural and chemically modified pineapple plant stem - Loh, Vivian Zing Ting (2019)
Pineapple plant stem (PPS) was used to sequester Pb(II), Cu(II) and Cd(II) from aqueous solution via adsorption. The PPS was chemically modified with organic acids and results showed the oxalic acid (OA) modified PPS (OAPPS) gave a better performance on the adsorption of Pb(II), Cu(II) and Cd(II) ions compared to natural PPS (NPPS). Both NPPS and OAPPS possessed hydroxyl, carbonyl and carboxyl functional moieties. The OAPPS has rougher surface and posed higher specific surface area than NPPS. NPPS and OAPPS have neutral surface charge at pH 4 and 2.4, respectively. The adsorption of Pb(II), Cu(II) and Cd(II) on NPPS and OAPPS from single metal solution showed similar trends. The removal percentages of Pb(II), Cu(II) and Cd(II) reached equilibrium at 0.05 g in 25mL adsorbate solution and optimum adsorption were noted at pH 4 – 6. The adsorption capacities of NPPS and OAPPS for Pb(II), Cu(II) and Cd(II) increased with the adsorbate concentration and reached maximum capacities at the equilibrium time of 30 – 90 min. The experimental data were found to best fitted with pseudo-second order kinetics model and Langmuir isotherm model. The maximum monolayer adsorption capacities of NPPS were 14.09, 5.08, and 1.50 mg/g while OAPPS achieved at 30.96, 8.54, and 3.64 mg/g for Pb(II), Cu(II), and Cd(II), respectively. The increase of temperature lowered the adsorption capacities of NPPS and OAPPS for Cu(II) and Cd(II) ions but enhanced the Pb(II) adsorption, suggested that Pb(II) adsorption is endothermic while Cu(II) and Cd(II) adsorption are exothermic reactions in nature. The interference ions in aqueous solution reduced the adsorption capacities of NPPS and OAPPS for Cu(II). Surprisingly, these co-existing ions enhanced the adsorption performance of NPPS for Pb(II) and Cd(II) in aqueous solution, however, it did not happen the same on OAPPS. The acid medium was found to be a better eluent for the regeneration of exhausted adsorbents and NPPS and OAPPS could be reused for 3 consecutive cycles.The surface complexation, electrostatic attraction, physisorption and chemisorption were elucidated for the adsorption of Pb(II), Cu(II) and Cd(II) on NPPS and OAPPS. The adsorption of Pb(II), Cu(II) and Cd(II) from aqueous solution using NPPS and OAPPS were carried in binary and ternary metal system as well. The results showed that the effect of binary and ternary metal system on the adsorption capacity of NPPS and OAPPS was antagonistic as the adsorption capacity of both adsorbents decreased when the system changed from single to binary or ternary. The NPPS and OAPPS adsorbed the metal ions in the order of Pb(II) > Cu(II) > Cd(II). Finally, NPPS and OAPPS were applied in real wastewater from textile industry and both adsorbents showed their ability to adsorb Pb(II) and Cd(II) from the wastewater. In general, the results proposed that PPS has more room for improvement and could be a potential adsorbent for Pb(II), Cu(II) and Cd(II) elimination from aqueous solution.